Cardiac complications of arteriovenous fistulas in patients with end-stage renal disease - Mohamad Alkhouli; Paul Sandhu; Khlaed Boobes; Kamel Hatahet; Farhan Raza; Yousef Boobes (Nefrología (English Edition), 2015)
Cardiovascular disease is the leading cause of the death in dialysis patients. Arteriovenous fistulas (AVFs) are associated with lower mortality and are viewed as the desired access option in most patients with advanced kidney disease needing dialysis. However, AVFs have significant and potentially deleterious effects on cardiac functions particularly in the setting of preexisting heart disease. This article provides a comprehensive and contemporary review to what is known about the impact of AVFs on: congestive heart failure, left ventricular hypertrophy, pulmonary hypertension, right ventricular dysfunction, coronary artery disease and valvular heart disease.